Nutraceuticals: A Holistic Approach to Health - Gohil, Dilsar (Asian Journal of Pharmaceutics (AJP), 2024)
Nutraceuticals, bridging nutrition and medicine, form a billion-dollar global industry. With dissatisfaction over costly medical treatments, consumers turn to healthier diets and nutraceuticals for an alternative. Recent scientific advances introduce concepts such as nutraceuticals, promising disease prevention, and reduced health-care costs. These compounds, categorized by natural sources, offer personalized, long-term solutions with a focus on holistic health. They play key roles in managing conditions from cardiovascular issues to neurodegenerative diseases, reducing oxidative stress, inhibiting cancer cell growth, and boosting cognitive function. As we look forward, genetics and personalized medicine will customize nutraceutical interventions, and the market for functional foods and plant-based nutraceuticals will expand as consumers seek healthier options. Ongoing research, technology, and regulatory standards will continue shaping healthcare’s future, making nutraceuticals a key player in disease prevention and holistic well-being